The Development of Digital Library Platform in Indonesian School Library - Nurhikmah Nurhikmah H; Arismunandar Arismunandar; Hadiwijaya Hadi; Mustafa Mustafa; Amrah Amrah; Abdul Malik Ramli (STAI Hubbulwathan Duri, 2023)
The purposes of this research are to find the needs of Digital Library Application Development, to create the prototype of Digital Library Application Development and to find the validation level, practicality, and effectiveness of Digital Library Application Development. This research method used Research and Development, which uses ADDIE (analysis, Design, Development, Implementation, Evaluation). The subjects of this research were 1 expert, 1 media expert, 1 leader, 4 librarians, 10 teachers, and 35 students. The method of collecting data used in this research were interviews, observation, and questionnaires. Based on the result of this research, it shows that the digital library application development is necessary to improve the learning and teaching process, with the centralized database, it can help the users access the information and help the librarian to manage the school library. The prototype of the library application development of Athirah Islamic School provides some descriptions that the library application is suitable for the users' needs. The testing result by the expert shows that the digital library application of Athirah Islamic School has fulfilled the very valid category through some field-testing steps such as content validation and media validation. The level of practicality of digital library application can be seen from the testing result of the product based on the technical aspect given by the practitioners (libraries, students, and teachers) that fulfills the strongly agree criteria or very practical category. The level of effectiveness of the library application use can be seen from the questionnaire results given to the students, teachers, and librarians. It can be concluded that of 5 indicators such as: system quality, information quality, serving quality, users' satisfaction and the net benefit obtained that the library application is at a very effective qualification level.